IMPLEMNETASI MODEL PEMBELAJARAN EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V-C SDN DUKUH MENANGGAL 1IMPLEMNETASI MODEL PEMBELAJARAN EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V-C SDN DUKUH MENANGGAL 1 (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study is (a) to find out the effect of experimental learning methods on student learning outcomes in class V-C, (b) Knowing the level of mastery of healthy thematic subject matter is important by applying the experimental method. This study uses two rounds of action research. Each round consists of two stages, namely: design, activities and observations, reflections and refissions. The target of this research is V-C Class Students of Dukuh Menanggal I Surabaya Elementary School in 2018-2019 Academic Year. The results showed that learning by applying experimental learning methods obtained the following results, the average value of student achievement in the first cycle reached 76.35 and in the second cycle scored 84.53. Meanwhile, classical completeness in cycle I obtained a percentage of 75% and cycle II of 93.75%. The conclusion of this research is that the experimental learning method can positively influence the improvement of the learning outcomes of the V-C class of SDN Dukuh Menanggal I Surabaya in the 2018-2019 academic year, and this learning model can be used as an alternativ tematik learning.